2013
DOI: 10.1002/2013jc009067
|View full text |Cite
|
Sign up to set email alerts
|

EN4: Quality controlled ocean temperature and salinity profiles and monthly objective analyses with uncertainty estimates

Abstract: [1] We present version 4 of the Met Office Hadley Centre ''EN'' series of data sets of global quality controlled ocean temperature and salinity profiles and monthly objective analyses, which covers the period 1900 to present. We briefly describe the EN4 data sources, processing, quality control procedures, and the method of generating the analyses. In particular, we highlight improvements relative to previous versions, which include a new duplicate profile removal procedure and the inclusion of three new quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
1,137
0
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,362 publications
(1,269 citation statements)
references
References 38 publications
20
1,137
0
8
Order By: Relevance
“…3. Additional VAT time series computed from two observational data sets from EN4.2.0 (Good et al 2013) are shown for examining differences in quality control procedures between EN4.2.0 300 m and from 100 to 500 m at greater depths as the grid of Levitus et al (1994) was adopted. Observed values averaged in the boxes were not vertically interpolated at the 28 levels.…”
Section: Accuracy Of Global Upper Ocean Heat Content Estimation Expecmentioning
confidence: 99%
“…3. Additional VAT time series computed from two observational data sets from EN4.2.0 (Good et al 2013) are shown for examining differences in quality control procedures between EN4.2.0 300 m and from 100 to 500 m at greater depths as the grid of Levitus et al (1994) was adopted. Observed values averaged in the boxes were not vertically interpolated at the 28 levels.…”
Section: Accuracy Of Global Upper Ocean Heat Content Estimation Expecmentioning
confidence: 99%
“…Subsurface temperatures are taken from the EN4 quality-controlled subsurface ocean temperature and salinity profiles and objective analysis dataset (Good et al 2013) provided by the Met Office Hadley Center (http://www.metoffice.gov.uk/hadobs/en4/). For both datasets, we use information for the time period 1960-2007 at monthly resolution.…”
Section: A Observational Datasetsmentioning
confidence: 99%
“…We focus our observational analysis on the period 1982-2012, over which both in situ and satellite observations of SSTs 22 and sea-surface heat fluxes 23 (SHFs) are available and ocean temperature measurements 24 have reasonable coverage within the SO (Methods). Rapid surface warming is seen in zonal bands along the northern flank of the ACC, with slower warming and cooling to the south (Fig.…”
mentioning
confidence: 99%
“…The GCMs simulate somewhat more Southern Hemispheric ocean heat storage (0.64 ± 0.21 Wm −2 ) than is observed over this period (0.57 Wm −2 from ref. 24 ; Supplementary Information), possibly due to model deficiencies or to observational biases introduced by infilling data-sparse regions of the ocean 2,25 . Yet, they robustly capture the overall patterns of heat storage, with substantial warming in the vicinity of the ACC and less warming to the south (Figs.…”
mentioning
confidence: 99%